Molecular Simulation of Hyperbranched Polyester - Yanmei, Liu; Haihua, Li; Yulei, Tai; Guoku, Chao; Yajuan, Zhao (JOURNAL OF ADVANCES IN CHEMISTRY, 2009)
A new types of hyperbranched polyester was synthesized by the 2,2-bis(hydroxymethyl) propionic acid as an AB2-type monomer and glycerol as the core moiety. Molecular weights were confirmed by Gel Permeation Chromatography. Acid values were titrated by KOH. The hydroxy value was obtained by titration. Furthermore, we calculate logarithmic value of acid value, hydroxy value, and molecular weight, respectively, and the simulation model curves were obtained. Based on the simulation model curves, we establish the empirical equation of the relationship of molecular weight, acid value and hydroxy value.